In vitro haemostatic activity of Rhodomyrtus Tomentosa (Aiton) Hassk. Aqueous leaf extract / Norizzaty Adli - Adli, Norizzaty (2015)
Thromboembolic is a disorder which rose up from the abnormal haemostasis process. Most of anticoagulant drug used in the treatment and prevention of thromboembolic disorder caused side effects such as bleeding. Potential of Rhodomyrtus tomentosa as a native anticoagulant been tested by evaluating the possible haemostatic effect of Rhodomyrtus tomentosa aqueous leaf extract in vitro. In vitro coagulation assays such as Thrombin time (TT), Prothrombin time (PT) and Activated partial thromboplastin time (APTT) tests were performed on normal coagulation control plasma spiked with different concentrations of the aqueous leaf extract (10 - 100%). Total tannin and flavonoid for all different concentrations of leaf extract were measured using spectrophotometer and correlate with clotting times (TT, PT and APTT). The results were analyzed using one way ANOVA followed by post-hoc Dunnet's and Pearson's correlation. The results showed that TT, PT and APTT of normal coagulation control plasma spiked with extract were markedly prolonged. A significant anticoagulant (p < 0.05) showed by PT was at lowest concentration (10%), TT was at concentration 50 - 100% and APTT was at concentration 80% 100%. The aqueous extraction showed a better anticoagulant for PT. The clotting times for TT, PT and APTT were significantly correlated (p < 0.05) with total tannin and flavonoid. Besides, the total tannin and flavonoid was significantly decreased (p < 0.05) when exposed to the light for 5 days. In conclusion, the results highlights that Rhodomyrtus tomentosa contain anticoagulant properties reflected the bioactive compound of tannin and flavonoid.